Measurement of the π0 electromagnetic transition form factor slope - Lazzeroni, Cristina; Gersabeck, Evelina (Physics letters, 2017)
The NA62 experiment collected a large sample of charged kaon decays in 2007 with a highly efficient trigger for decays into electrons. A measurement o…